An Oxygen‐Resistant and Self‐Eliminating Passivated Layer for Highly Stable Lithium Metal Batteries. (12th February 2022) - Zhu, Maogen; Fan, Zhechen; Xu, Kangli; Fang, Yuting; Sun, Wei; Zhu, Yongchun
Abstract: Lithium‐metal batteries show great promise as the next generation rechargeable batteries with high theoretical energy density. Unfortunately, Li metal anodes suffer from serious corrosion of the electrolyte and by‐products shuttled from cathode during cycling, such as O2 in Li‐O2 batteries. Here, an oxygen‐resistant and self‐eliminating passivated layer is fabricated through a Wurtz‐type reaction between Li metal and dichlorodimethylsilane (DCDMS). This passivated layer guarantees Li metal great stability with O2 and inhibits the dendritic growth by eliminating the unpredictable fresh Li dendrites in their infancy stage. In addition, this passivated layer is constructed of LiCl and Poly(dimethylsilylene) phases, which provide good Li + transport, self‐eliminate the undesirable by‐products. The symmetric battery with this protective layer can achieve a stable Li plating/stripping with 500 h at O2 atmosphere. Consequently, the Li‐O2 battery can maintain a stable cycling with more than 200 times and the Li||NCM811 battery presents excellent cycling performance (300 cycles at 0.5 C) and rate capacity (130.3 mA h g −1 at 5 C). This work provides both material and method breakthroughs for the development of electrode protection, which promotes the practical application of silanes and its ramification in alkali metal batteries. Abstract : In this work, a facile method to construct a stable self‐eliminating passivated layer for Li metal batteries through a Wurtz‐type reaction between dichlorodimethylsilane and Li metal is shown. The generated passivated layer shows extreme stability with O2 and inhibits the growth by eliminating the unpredictable fresh Li dendrites in their infancy stage.